Complex thought: a challenge for the teacher and families today - Gomero Pretel, Veronikha Teresa (2019)
Today´s society requires to educational system to develop competencies in students, improving their well-being and quality of life in order to contribute to social, cultural, ethnic development of the families and the society. Thus, educator´s accompaniment is required for the planning and realization of personal life’s ethical project of each student. In this regard, it is sought that today’s the educators and families develop competences and show performances on complex thought skills, which allows them to understand the meaning of the pedagogical practices based on the knowledge of Jack Delors; learning to learn, to be, to coexist, to do and to live. Therefore, it is needed to share the experience in understanding the complex thought’s sense that is based on socio-formative approach and the complex thought method, in order to be applied in the pedagogical practices to generate learning for the life of diversity of the students in the school.